International business : five case-writings on Government-Linked Corporations based in Asia. - Tan, Wee Meng. (2008)
This Applied Research Project (ARP) consists of five International Business cases dealing with five government-linked companies (GLCs) located Asian countries. Meanwhile, the areas of emphasis vary from case to case, depending on each company’s unique characteristics. Our project hopes to make contribution to the academic arena by writing new and updated cases especially addressing the effect of the Asian Crisis on these selected Asian companies.